A comparison of transcatheter aortic valve implantation and surgical aortic valve replacement in 1,141 patients with severe symptomatic aortic stenosis and less than high risk - Schymik, Gerhard; Pilz, Lothar R.; Süselbeck, Tim (Catheterization and cardiovascular interventions, 2015)
Objectives To assess outcomes for patients undergoing transcatheter aortic valve implantation (TAVI) versus surgical aortic valve replacement but with less than high risk. Background While there is abundant data for high risk patients there is insufficient data for reduced risk. Methods Patients undergoing TAVI or SAVR between 2007 and 2012 in Karlsruhe were considered. They were assessed by cardiac computed tomography, transoesophageal echocardiogram, and logistic EuroSCORE I (ES) and groups compared using Propensity Score Matching. Results The mean ES was 10.1±2.8 in the TAVI group (n?=?419) and 5.7?±?3.2 in the SAVR group (n?=?722; P?